Design and development of novel polypropylene based aluminium-air battery system - Tan, Weng Cheong (2023)
The global energy demand is increasing rapidly due to the rapid development and adoption of new technologies in every sector. Therefore, there is a need to introduce a clean energy source that does not harm the environment. Metal-air batteries have gained significant attention as promising storage system for the post lithium-ion era. These batteries generate electricity through oxidation and reduction reactions within the anode and cathode. Among various types of metal-air batteries, the aluminium-air battery is particularly attractive due to its high energy density and environmental friendliness. In this study, a novel polypropylene-based aluminium-air battery is developed. Polypropylene pads are utilized to absorb the electrolyte, isolate the anode and cathode, and reduce the hydrogen generation in the parasitic reaction. Two different types of electrolyte systems namely single electrolyte system and dual electrolyte system are analysed. The performance of the aluminum-air battery will be investigated using various electrochemical techniques, such as discharge tests, polarization tests, electrochemical impedance spectroscopy, and Tafel analysis. Next, surface morphology characterization of the aluminum anode and polypropylene will be performed using SEM and XRD. The single electrolyte system aluminium-air battery is constructed with an aluminium foil anode, a carbon fiber cloth aircathode, and a polypropylene separator. The effects of electrolyte concentration on the aluminium-air battery are investigated and analyzed using various discharge currents. The study reveals a negative correlation between battery capacity and electrolyte concentration. At discharge current of 30 mA, the aluminium-air battery achieves a specific capacity of 375 mAh.g-1 when 1M potassium hydroxide is used as the electrolyte. In the dual electrolyte system, potassium hydroxide is used as the anolyte and sulfuric acid is used as the catholyte. A parametric study is conducted to investigate the effect of electrolyte concentration and polypropylene separator thickness on battery performance. The results demonstrated that the dual-electrolyte system can increase the open circuit voltage to 2.2 V compared to the single electrolyte system when using 5M anolyte, while maintaining a specific discharge capacity of about 1390.92 mAh.g−1. Furthermore, the maximum peak power density significantly increases from 100 mW.cm−2 to 350 mW cm−2 for the dual electrolyte system.Tafel analysis has shown that the concentration of KOH electrolyte used in the aluminum-air battery affects the corrosion rate of the aluminum anode. Specifically, a higher concentration of electrolyte increases the corrosion rate. On the other hand, the polypropylene pad has demonstrated superior performance in limiting the corrosion rate of the aluminum-air battery, reducing it by up to 89.1% when compared to the case without a polypropylene separator.